One-millisecond low-cost synchronization of wireless sensor network - Linhares, Robson; Lima, Carlos R. E.; Renaux, Douglas; Pottker, Fabiana; Oroski, Elder; Lazzaretti, Andre; Mulinari, Bruna; Ancelmo, Hellen; Gamba, Adriano; Bernardi, Luiz; Lima, Lucas (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
Precise time synchronization is an important requirement for a wide set of distributed applications in which timestamped data should be produced by distributed nodes and then correlated with a limited amount of timing. There are several techniques and protocols that address this issue, however, most of them rely on specialized hardware and/or software solutions, thus incurring on relatively high cost to deploy a synchronization network. In this paper, a low cost approach to synchronize a network of wireless sensors is proposed and applied in the context of an electrical power monitoring system, which is then used to build a dataset that supports research in the area of Non-Intrusive Load Monitoring (NILM). The monitoring system is designed to detect load events on several distributed nodes of a power circuit and to synchronize, with a millisecond precision, the voltage and current data collected on them. Results show that such a precision can be achieved with simple and relatively low-cost hardware, enabling this solution to be used on several contexts where the budget and time requirements are important concerns.